2019
DOI: 10.21037/tlcr.2019.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-based EGFR genotyping in bronchoalveolar lavage fluid from treatment-naive non-small cell lung cancer patients

Abstract: Background: Extracellular vesicles (EV) have been proven to contain double-stranded DNA reflecting the mutational status of the parental tumor cells in non-small cell lung cancer (NSCLC), which can be translated into clinically useful EV-based liquid biopsy for Epidermal growth factor receptor (EGFR) genotyping using bronchoalveolar lavage fluid (BALF) obtained from tumor site.Methods: Patients subjected for an initial lung cancer work-up underwent bronchoscopy and BALF was obtained from tumor site. After isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…This study also highlighted the ongoing diagnostic and prognostic ability of EV DNA by showing that the mutations identifiable by EV DNA liquid biopsy included the acquired resistance specific mutation T790M. Furthermore, the specificity and sensitivity of liquid biopsy increased even more with the use of BALF EV DNA [16,76]. Similar to NSCLC, analysis of serum EV DNA from pancreatic cancer patients also demonstrated the presence of clinically relevant KRAS-specific mutations [14,77,78].…”
Section: Advantages Of Extracellular Vesiclementioning
confidence: 73%
See 2 more Smart Citations
“…This study also highlighted the ongoing diagnostic and prognostic ability of EV DNA by showing that the mutations identifiable by EV DNA liquid biopsy included the acquired resistance specific mutation T790M. Furthermore, the specificity and sensitivity of liquid biopsy increased even more with the use of BALF EV DNA [16,76]. Similar to NSCLC, analysis of serum EV DNA from pancreatic cancer patients also demonstrated the presence of clinically relevant KRAS-specific mutations [14,77,78].…”
Section: Advantages Of Extracellular Vesiclementioning
confidence: 73%
“…In a study performed with pathologically confirmed NSCLC patients, the sensitivity and specificity of BALF EV-based EGFR genotyping were high, and this assay showed an even better mutation detection rate than tissue/cytology-based typing. Also, the sensitivity increased as the stage progressed, reaching 100% with stage IV patient samples [76]. These results seem to suggest BALF EV-based EGFR genotyping is a highly promising liquid biopsy method, and particularly efficient for patients that require repeat biopsies throughout progression of the disease.…”
Section: Liquid Biopsy Using Bronchoalveolar Lavage Fluidmentioning
confidence: 81%
See 1 more Smart Citation
“…Obtaining these kinds of liquid biopsies might be beneficial since body fluids derived from the proximity of the primary tumor bear the potential to better represent the molecular landscape of the tumor which would increase sensitivity and specificity of the diagnosis [87,96,103]. For example, EGFR genotyping of EVs of bronchoalveolar lavage fluid of NSCLC patients showed superior sensitivity and accuracy compared to plasma EV DNA genotyping [79]. These results suggest that this might also apply to ncRNA analysis of proximal fluids compared to EVs obtained from plasma or serum.…”
Section: Characterization and Importance Of Extracellular Vesicle (Evmentioning
confidence: 99%
“…Current studies focus on the extracellular vesicles mainly isolated from human blood, or, respectively, serum or plasma [ 71 , 72 , 73 , 74 ]. However, extracellular vesicles can be isolated from a broad variety of human body fluids such as urine [ 75 , 76 ], saliva [ 77 , 78 ], bronchoalveolar liquid [ 79 ], pleural lavage [ 80 ], and cerebrospinal fluid [ 81 ] and even more uncommon ones like tears [ 82 ], semen [ 83 ], menstrual blood [ 84 ], peritoneal lavage [ 85 , 86 ], bile [ 87 ], and pancreatic juice [ 88 ]. An overview of non-coding RNAs that were analyzed in extracellular vesicles isolated from different liquid biopsies of different kinds is presented in Table 1 .…”
Section: Characterization and Importance Of Extracellular Vesiclementioning
confidence: 99%